HUBUNGAN PENGGUNAAN STANDAR RESEP DAN BAHAN BAKU MAKANAN DENGAN KUALITAS PRODUK MAKANAN PADA RESTORAN HOTEL BINTANG EMPAT DI KOTA BANDUNG - Widya Astuti Hidayat, - (2009)
This observation was applied to 11 four-star restaurant hotel, observer's target is the chef as standard recipe and raw food material's user with its correlation with food quality product, use 10 respondent in average. This observation's purpose is to find out the correlation As independent variable is using standard recipe (X1) and raw food material (X2). Dependent variable is (Y) quality food product on four-star restaurant hotel in Bandung. Based on the observation variety which are descriptive and verification, this observation use Explanatory survey method. By use sample and questionnaire as data research tool. And use Kendall-Tau for technique analysis. Based on statistic's count, correlation coefficient for Kendall between the use of standard recipe (X1) with quality food product (Y) is 0,818, between raw material use (X2) with quality food product (Y) for 0,273. For Konkordansi W analysis is 0,651. Observer suggest that restaurant hotel for always use standard recipe to produce standardization quality food and the use of raw material is very important so it is suggested to use standardization raw material in standard recipe, standard purchase, standard storage, and the use of raw material standard.